Igualdade e discriminação e o direito fundamental à educação: o acesso ao ensino superior e o sistema de cotas - Quilis, Rita de Cássia Zangerolamo (2009)
This present work was done to ascertain concepts, chains and doctrines concerning the Principle of Equality and Discrimination; having the fundamental right to educations main capacity turned to Superior Education and the System of Quotas. Analyzing the Principle of Equality and Discrimination in all Brazilian Constitution, from the Empire until the actual valid Federative; accepting the starting point of doctrines and the home land legislations, always, the equality in the presence of the law. Inside the Fundamental Right of Education, an historical analyzes of past Constitutions. We present the pros and cons of the program that inserts the system of quotas on the, public and private universities, further analyzing the temporary measures, the actual laws and the jurisprudences. We defend the acceptance on an university thru a meritocratic system, thru the governmental politics of elementary and middle schools of public education, that would prepare an individual since childhood, so one have the intellectual condition to dispute a place in a public or private university, in equality and condition of the candidate that had attended a private elementary and middle schools. At last, we have to improve our public elementary and middle schools, so that the students will get to a superior education, thru their own merits, without depending on palliatives or discriminatory measures